Study of photonic band-gap structure in three component Fibonacci multilayers - Mishra R.K.; Pandey P.C. (My University, 2025)
In this paper, photonic band-gap structures of three-component Fibonacci multilayers are presented for the first time with the help of reflection and transmission diagrams. Here, a general method (method of transfer matrices) is used to describe dispersion, reflection, and transmission spectral studies. Quantitative analysis for the distribution of allowed and forbidden bands for different generation numbers is also demonstrated. The effect of an imaginary value for the propagation vector Q as well as an increase in the size of the system on the existence of forbidden photonic bands in the case of normal radiation of light in these lattices is also studied. © 2008 NRC Canada.